Wafer-scale vertically aligned carbon nanotubes for broadband terahertz wave absorption - Sun, Leimeng (2021)
Materials with high and broadband absorption characteristics in the terahertz (THz) range are desirable for many applications. In this paper, we propose, fabricate and experimentally demonstrated a wafer-scale vertically aligned carbon nanotube (VACNT) array for broadband THz wave absorption. The effects of VACNT parameters on the absorption performance are investigated within the THz and infrared spectra using the Maxwell-Garnett theory, revealing that the absorption in the THz range can be greatly enhanced by suitable selections of the length, volume fraction and vertical alignment factor of CNTs. A VACNT array with an average CNT length of ∼600 μm is fabricated on a 4-inch silicon substrate. Experimental results measured by a THz time-domain spectroscopic system show an average power absorptance of ∼98% from 0.3 to 2.5 THz, and agree well with the numerical modelling. This device can be used as a cost-effective near-perfect absorber across the THz and infrared regions for thermal emission and imaging, electromagnetic interference shielding, stealth and energy harvesting applications.